Psychiatric manifestations of neurologic disease: where are we headed? - Lyketsos, Constantin G. (Les Laboratoires Servier, 2007)
Neuropsychiatry represents a field of medicine situated at the crossroads of neurology and psychiatry, and deals with the interface of behavioral phenomena driven by brain dysfunction. Psychiatric symptoms are highly prevalent in these conditions, are a major source of disability and diminished quality of life, and potentially represent the target of treatment interventions that stand to significantly decrease the suffering they generate. In this article, the disease paradigm is explained, with particular attention to its role as an organizing principle for the field. Specific diseases including traumatic brain injury, stroke, Parkinson's disease, Alzheimer's disease, multiple sclerosis, and epilepsy are explored in relation to the presentation of multiple psychiatric phenotypes in each, associations with underlying brain pathology, and existing treatment approaches. Finally, the afticle explores the inherent complexities in this area of research and proposes a framework for future work based on the understanding of phenomenology and associated risk factors, the involvement of the rapidly advancing field of neuroscience, and targeted treatment development to serve as a road map for advancement in the field.